Analisis ICC Jurisdiction Analysis of the Legalization of the Russian President's Arrest Warrant in View of International Law - Sa'adatul Ummah; Priyambodo Adi Saputro; Cholidah, Cholidah (Journal of Law, Politic and Humanities, 2024)
This research aims to analyze the ICC Jurisdiction and the Legalization of the Arrest Warrant for the President of Russia Based on the Principles of International Law of the 1998 Rome Statute and the Russian Party's Rejection of the ICC's Arrest Warrant, so this research was conducted to find out this. The method used in this research is a juridical normative type research method where this journal examines concepts, rules, principles, theories and statutory regulations as well as the opinions of existing legal experts which relate to the form of ICC jurisdiction based on the Statute. Rome 1998 from the perspective of International Law. As well as using a Conceptual Approach where material is obtained from literature such as books, journals, articles and so on which discuss this research problem. ICC (International Criminal Court) is an International Criminal Court established through the 1998 Rome Statute in The Hague, Netherlands. In its jurisdiction, the ICC can only try countries that recognize its jurisdiction which, based on the 1998 Rome Statute, outside of its jurisdiction, the ICC does not have the right to try(Dhuara, 2021). With this in mind, the issues raised in this research are as follows: 1. How to legalize the arrest warrant for Russian President Vladimir Putin, who is not a member country of the ICC or a country that has ratified the Rome Statute; 2. What is the basis for the Russian President's rejection of the Arrest Warrant based on International Law.